Developing Criteria for Selecting Secondary School Principals in Palestine - Abed Atallah Abed Hamayel (My University, 2000)
The present study aimed at developing proposed educational criteria for the selection of the teachers at UNRWA Schools in north of Palestine. Accordingly, it tried to answer the following basic questions: 1- What is the exact level of the proposed educational criteria for the selection of the teachers at UNRWA Schools in the north of Palestine from the points of the population of the study? 2- What is the exact hierarchy of the proposed criteria for the selection of teachers at UNRWA Schools in north of Palestine with respect to their importance? 3- Are there significant differences in the proposed educational criteria for the selection of the teachers at UNRWA Schools in north of Palestine from the points of view of the population of the study attributed to the following variables: qualifications, the administrative experience, sex. The population of the study included all the principals at UNRWA schools in north of Palestine in the scholastic year 2000-2001. The total number was (86) principals distributed to three areas: Nablus, Jerusalem/Ramalla and Hebron. To achieve the purposes (of the study, the researcher himself developed a questionnaire after surveying the related literature. The validity of this questionnaire was judged by a jury of specialists who confirmed its validity. As for the reliability, it was computed by using Cronbach Alpha. It was found to be (.92). The questionnaire consisted of 89 items distributed to 17 factors . The questionnaire used the Likard's scale: strongly agree, agree, neutral, disagree and strongly disagree. It should be noted that those five levels were hierarchically graded from five to one. With respect to the statistical analysis, the following were used: -The percentage, the statistical mean and the standard deviation were used to all the questions of the study. 1- 14 criteria out of the 17 criteria of the study were strongly agreed upon by more than 80%. 2- Three criteria were agreed upon by more than 70%. 3- The most five high criteria were hierarchically ordered with their respect to their importance: -The profession manners. -Guidance and counseling. -Time management. -Human and educational relations. -The way of selection of the basic grade teachers. The study showed that there are differences belong to a change. Qualifications: more than 80% of the principals with diploma degrees highly agreed those criteria in comparison to other degrees. Administrative experience: more than 80% of the principals with more than 15 years’ experience strongly agreed those criteria in comparison to other levels of experience. Sex: more than 80% of female principals highly agreed those criteria in comparison to the male. On the basis of the results of this study, the researcher hopes: 1- Those in charge should consider these proposed criteria in the selection of the teachers of UNRWA schools. 2- Those in charge of the programs of teachers training in the colleges and universities should take into account these proposed criteria , and apply them as indispensable components of training programs.

هدفت هذه الدراسة إلى تطوير معايير تربوية مقترحة يمكن الرجوع إليها عند اختيار مديري المدارس الثانوية في فلسطين وقد حاولت الدراسة الإجابة عن السؤال الرئيسي التالي:- • ما مستوى درجة المعايير التربوية المقترحة لاختيار مديري المدارس الثانوية في فلسطين من وجهة نظر مديري التربية والتعليم ومساعديهم الإداريين والفنيين، ورؤساء أقسام التعليم العام والإشراف التربوي؟ • هل يوجد اختلاف في مستوى درجة تصورات أفراد مجتمع الدراسة للمعايير التربوية المقترحة لاختيار مديري المدارس لثانوية في فلسطين، يعزى للمتغيرات التالية:- • متغير المستوى الإداري. وله مستويات: (مديرو التربية والتعليم ومساعدوهم الإداريون والفنيون، ورؤساء أقسام التعليم العام والإشراف التربوي). • متغير المؤهل العلمي وله مستويان: (بكالوريوس فما دون، دراسات عليا). • متغير سنوات الخبرة التربوية. ولها ثلاث مستويات: (أقل من 10 سنوات، من 10 سنوات إلى15 سنة، أكثر من 15سنة). • وتكون مجتمع الدراسة من جميع مديري التربية والتعليم ومساعديهم الإداريين والفنيين، ورؤساء أقسام التعليم العام والإشراف التربوي، في جميع مديريات التربية والتعليم المنتشرة في المحافظات الفلسطينية خلال شهر تشرين أول من العام الدراسي 1999-2000م والبالغ عددهم (69) إداريا موزعين على (15) مديرية. • ولتحقيق أهداف الدراسة قام الباحث باستخدام استبانة طورها بنفسه معتمدا على الأدب التربوي والدراسات السابقة في الموضوع، اشتملت على (140) فقرة (معياراً) على (24) مجالا، وتأكد من صدقها بالتحكيم، ومن ثباتها الكلي باستخدام معادلة كرومباخ ألفا على عينة تعدادها (20) إداريا من أفراد مجتمع الدراسة، حيث وصل ثباتها الكلي إلى (0.95). • وتكون سلم الاستبانة من خمسة مستويات للإجابة (أوافق بشدة. أوافق. محايد أعارض. أعارض بشدة). بحيث تم تخصيص (خمس) درجات للمستوى الأول و(أربع) درجات للمستوى الثاني، و(ثلاث) درجات للمستوى الثالث و(درجتان) للمستوى الرابع ودرجة (واحدة) للمستوى الخامس. واستخدم الباحث التحاليل الإحصائية التالية:- • المتوسطات الحسابية والنسب المئوية لكل فقرة والدرجة الكلية لكل مجال للإجابة عن السؤال الأول والثاني والثالث. • المتوسطات الحسابية والانحرافات المعيارية لكل فقرة والدرجة الكلية لكل مجال للإجابة عن السؤال الرابع (متغيرات الدراسة). وتوصلت الدراسة إلى النتائج التالية:- • أولاً: خمسة عشر مجالاً من بين أربعة وعشرين حصلت على درجة موافقة (كبيرة جداً) بنسبة مئوية أكثر من (80%). • ثانيا: ثمانية مجالات حصلت على درجة موافقة (كبيرة) بنسبة مئوية أكثر من (70%). • ثالثاً: مجالاً واحداً حصل على درجة موافقة (قليلة) بنسبة مئوية أكثر من (50%). وأما فيما يتعلق بنتائج الدراسة تبعا لمتغيراتها. فقد توصلت الدراسة إلى النتائج التالية:- • أولا: متغير المستوى الإداري: كانت الفروق لصالح المستوى الإداري الأول (مديرو التربية والتعليم ومساعدوهم الإداريون والفنيون) بدرجة موافقة (كبيرة جدا) أكثر من (80%). • ثانياً متغير المؤهل العلمي: كانت الفروق لصالح المستوى الأول (بكالوريوس فما دون) بدرجة موافقة (كبيرة جداً) أكثر من (80%). • ثالثا: متغير سنوات الخبرة التربوية: كانت الفروق لصالح المستوى الثالث (أكثر من 80%). وخرجت الدراسة بالتوصيات التالية: 1. أن تأخذ وزارة التربية والتعليم والمديريات بهذه المعايير عند اختيار مديري المدارس الثانوية في فلسطين. واختيار المديرين من بين الحاصلين على مؤهل علمي جامعي وتأهيل مسلكي. وتأهيل المديرين المعينين. وتدريبهم على النمط الديمقراطي في القيادة. وتفويض صلاحيات الاختيار والتعيين لمديريات التربية. ومنح المديرين مزيداً من الصلاحيات في مدارسهم وإشراكهم في رسم السياسات التعليمية. وإيجاد مركز للمعلومات الإدارية. 2. يوصي الباحث بإجراء دراسة مشابهة لاختيار مديري المدارس الأساسية في فلسطين. ودراسة لمعرفة درجة تطبيق هذه المعايير. ودراسة حول الأسباب التي تؤدي إلى نجاح أو فشل مدير المدرسة الثانوية في عمله.
تطوير معايير تربوية مقترحة لاختيار مديري المدارس الثانوية في فلسطين